Study of the residual polymer-aluminum recycling process of carton packaging (Research, Society and Development, 2021)
The complexity of the structure of carton packs is one of the factors that hinder the development of processes for recycling after consumption. The few processes that are currently used do not manage to completely recycle all the materials used in these packages. The few economically viable processes are applied to the recycling of paper layers, leaving as a residue the combined layers of polyethylene and aluminum, known as polymer-aluminum residues (Poly-Al) from carton packs. In this context, a method for recycling polyethylene and aluminum present in Poly-Al residues from post-consumer carton packs was researched and developed using the alkaline aluminum digestion process. Solutions with different concentrations of NaOH were evaluated at an ambient temperature with a treatment time of 24 h. After the aluminum removal processes, the polyethylene films and the liquid and solid phases precipitated from the reaction medium were analyzed. Scanning electron microscopy (SEM/FEG), dispersive x-ray fluorescence energy spectroscopy (EDS), x-ray diffraction (XRD), inductively coupled plasma mass spectrometry (ICP) and calorimetry differential scanning (DSC) were used for the analyzes. The results indicated the removal of aluminum from polyethylene films from Poly-Al residues with good efficiency and without significantly compromising the thermal properties of the polymer.